Analisis Strategi Media Sosial Pemasaran Pada Platfrom Tiktok Celana @Jiniso.Id - febriana, Poppy; defliana, shinta nur (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study discusses the analysis of social media marketing on the TikTok pants platform @jiniso.id. The purpose of this study is to determine the social media marketing strategy used on the TikTok pants platform @jiniso.id. This study uses a qualitative method to analyze social media strategies on the TikTok platform. Data collection using Content Analysis is called identifying patterns or relationships in video analysis content on the TikTok pants account @Jiniso.id. So that the data source taken is a primary data source, the primary data source is a data source obtained from the results of observations on the TikTok account @Jiniso.id. Primary data sources are also obtained from documentation such as uploaded videos on the TikTok account @Jiniso.id. The data used consists of 758 uploaded videos from December 1, 2023 to March 30, 2024, with the author accurating 8 content that has been watched more than 1 million times to 2 million times according to other criteria. With this you can see, the results of research from content analysis using social media marketing theory reviewing social media marketing on the TikTok platform @Jiniso.id by applying 3 characteristics that are often used: Transparent, social networking, multi-opinion. Transparency is highlighted through the presentation of clear product information, such as detailed specifications and promotions, as well as direct communication via live streaming. Collaborations with popular influencers expand audience reach while creating emotional connections through casual and relatable interactions. Friendly responses from admins to customer comments strengthen positive relationships with consumers, and improve brand image. This strategy creates a pleasant shopping experience, builds trust, and increases customer engagement with the Jiniso brand.